Chemical studies towards the synthesis of janolusimide, a marine neurotoxin from janolus cristatus / Nurulhuda Kamaruddin - Kamaruddin, Nurulhuda (Institute of Graduate Studies, 2017)
Janolusimide 19 was chosen to be the synthetic target molecule due to having a unique tripeptide structure besides showing a neurotoxin activity. Our synthetic approach towards the synthesis of janolusimide involved the construction of a core lactam system derived from L-valine using EDC.HCl followed by dimethylation using four different conditions. Dimethylation at C-3 position of 133 affords (5S)-3,3- dimethyl-5-isopropylpyrrolidine-2,4-dione 26 in 72% yield using TBAF as a phase transfer catalyst. In this dimethylation step, a characteristic of ambident anion also can be observed. Multiple positions of alkylation had occurred due to enolate’s ambident character of which C,O-alkylated and O-alkylated side products were observed. While the effort to synthesize the dipeptide chain was carried out using aldol reaction, N-alkylation of 26 and N-acylation of a template, 2-pyrrolidinone 139 and lactam 26 with several electrophiles. Four general protocols (Method A-D) to N-acylate 2-pyrrolidinone and lactam 26 were examined..